2016
DOI: 10.1051/0004-6361/201528037
|View full text |Cite
|
Sign up to set email alerts
|

Fast outflows and star formation quenching in quasar host galaxies

Abstract: Negative feedback from active galactic nuclei (AGN) is considered a key mechanism in shaping galaxy evolution. Fast, extended outflows are frequently detected in the AGN host galaxies at all redshifts and luminosities, both in ionised and molecular gas. However, these outflows are only potentially able to quench star formation, and we are still lacking decisive evidence of negative feedback in action. Here we present observations obtained with the Spectrograph for INtegral Field Observations in the Near Infrar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

19
219
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 160 publications
(239 citation statements)
references
References 68 publications
19
219
1
Order By: Relevance
“…Instead, the extended sizes of the SMGs with the AGN-dominant class are puzzling. In line with the evolutionary scenarios of, e.g., Sanders et al (1988), Hopkins et al (2008), and Toft et al (2014) where SMGs evolve into QSOs, the extended sizes may be explained by positive AGN feedback by a growing supermassive black hole in the phase of star-formation quenching, as is suggested by simulations for luminous AGN/QSOs (e.g., Ishibashi & Fabian 2012;Zubovas et al 2013) and considered for some luminous QSOs (e.g., Carniani et al 2016). In fact, ASXDF1100.057.1, which is an SMG of the AGN-dominant class, has a QSO-like, near-IR morphology (Figure 4).…”
Section: Agn Growth During a Verysupporting
confidence: 60%
See 1 more Smart Citation
“…Instead, the extended sizes of the SMGs with the AGN-dominant class are puzzling. In line with the evolutionary scenarios of, e.g., Sanders et al (1988), Hopkins et al (2008), and Toft et al (2014) where SMGs evolve into QSOs, the extended sizes may be explained by positive AGN feedback by a growing supermassive black hole in the phase of star-formation quenching, as is suggested by simulations for luminous AGN/QSOs (e.g., Ishibashi & Fabian 2012;Zubovas et al 2013) and considered for some luminous QSOs (e.g., Carniani et al 2016). In fact, ASXDF1100.057.1, which is an SMG of the AGN-dominant class, has a QSO-like, near-IR morphology (Figure 4).…”
Section: Agn Growth During a Verysupporting
confidence: 60%
“…As a next step, it would be useful to test the hypothesis that SMGs are connected to the formation of the most massive galaxies, being triggered by major mergers, and then evolving into compact quiescent galaxies via quenching in a quasi-stellar object (QSO) phase (e.g., Sanders et al 1988;Hopkins et al 2008;Toft et al 2014). The compact submillimeter sizes of SMGs, including recent reports of the existence of subkiloparsec-scale starburst cores (Iono et al 2016;Ikarashi et al 2017;Oteo et al 2017), suggests that the intense starformation activity might be quenched by active galactic nuclei (AGN), as observed in some luminous QSOs (e.g., Maiolino et al 2012;Carniani et al 2016). However, previous X-ray (e.g., Alexander et al 2005;Wang et al 2013) and mid-infrared (IR; e.g., Ivison et al 2004;Coppin et al 2010;Serjeant et al 2010) studies indicate that some SMGs do harbor AGN.…”
Section: Introductionmentioning
confidence: 99%
“…Nesvadba et al 2006Nesvadba et al , 2008Harrison et al 2012Harrison et al , 2014Liu et al 2013;Carniani et al 2015;Perna et al 2015b) and infer their mass outflow rate and kinetic power, with measuredṀ andĖ kin up to ∼ 600 − 700 M ⊙ yr −1 and ∼ 0.01× L Bol , respectively. Furthermore, in some cases, the outflowing [OIII] emission has been found to be spatially anticorrelated with narrow Hα emission, which traces star formation in the host galaxy (Cano-Díaz et al 2012;Cresci et al 2015;Carniani et al 2016). These results are considered among the most compelling pieces of evidence of negative feedback from AGN reported so far.…”
Section: Introductionmentioning
confidence: 85%
“…Ionized, atomic and molecular outflows are commonly observed towards local and high-z quasars (e.g. Feruglio et al 2010;Rupke & Veilleux 2011;Carniani et al 2015Carniani et al , 2016Feruglio et al 2015, see also Fabian (2012 for a review on this subject). In particular, observations of the CO(1-0) emission line in local ultra-luminous galaxies have found that a non-negligible fraction (from few% up to 30%) of the total H2 mass is located in outflows extended on ∼kpc scales (Cicone et al 2014).…”
Section: Estimates Of Mhmentioning
confidence: 99%